Cerebral Near Infrared Spectroscopy Monitoring in Term Infants With Hypoxic Ischemic Encephalopathy—A Systematic Review - Mitra, Subhabrata; Bale, Gemma; Meek, Judith; Tachtsidis, Ilias; Robertson, Nicola J. (Frontiers in Neurology, 2020)
Background: Neonatal hypoxic-ischemic encephalopathy (HIE) remains a significant cause of mortality and morbidity worldwide. Cerebral near-infrared spectroscopy (NIRS) can provide cot side continuous information about changes in brain hemodynamics, oxygenation, and metabolism in real-time. Objective: To perform a systematic review of cerebral NIRS monitoring in term and near-term infants with HIE. Search methods: A systematic search was performed in Ovid EMBASE and Medline database from inception to November 2019. The search combined three broad categories: measurement (NIRS monitoring), disease condition (hypoxic-ischemic encephalopathy (HIE)) and subject category (newborn infants) using a stepwise approach as per PRISMA guidance. Selection criteria: Only human studies published in English were included. Data collection and analysis: Two authors independently selected, assessed the quality and extracted data from the studies for this review. Results: Forty-seven studies on the term and near-term infants following HIE were identified. Most studies measured multi-distance NIRS based cerebral tissue saturation using monitors that are referred to as cerebral oximeters. Thirty-nine studies were published since 2010; 8 studies were published before this. Only six studies reviewed the neurodevelopmental outcome in relation to NIRS findings. No randomized study was identified. Conclusion: Commercial NIRS cerebral oximeters can provide important information regarding changes in cerebral oxygenation and hemodynamics following HIE and can be particularly helpful when used in combination with other neuromonitoring tools. Optical measurements of brain metabolism using broadband NIRS and cerebral blood flow using diffuse correlation spectroscopy add additional pathophysiological information. Further randomized clinical trials and large observational studies are necessary with proper study design to assess the utility of NIRS in predicting neurodevelopmental outcome and guiding therapeutic interventions.